GOOD MANUFACTURING PRACTICES (GMP) IN SMALL ENTERPRISE OF MILKFISH SATAY - Zulfatun Najah; Gita Dwi Lestari; Ahmad Mujaki Diwan; Muhammad Dhabit Dzikribillah; Muhammad Rizal Febriansah; Rita Purnamasari; Dian Anggraeni (University of Sultan Ageng Tirtayasa, 2020)
Milkfish satay is indigenous food product from Banten Province. Quality assurance in the milkfish satay production need tobe improved, especially in the sanitation and food safety. Basic eligibility Program in the fish industry is needed to ensure food safety, namely sanitation standard operating procedures (Sanitation Standard Operating Procedures/SSOP) and the good food production (Good Manufacturing Practices / GMP. Good manufacturing practices (GMP) is a guideline for the food industry to produce food and beverages that are safe, have a high quality, and feasible for consumption. The purpose of this study was to examine the implementation of GMP on milkfish satay production. This study is conducted by doing interview with owner followed by observation and documentation of all activities related to the production process in order to examine the GMP applied. The result showed that the production activity of Milkfish Satay used traditional method. The small enterprise has to improve the GMP practices in the criteria of building and facilities, equipment, hygiene and sanitation facities, activities, health and workers hygiene, label, process control, recording and documentation.